2012
DOI: 10.1111/j.1502-3931.2012.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Micromammal biostratigraphy of the Upper Miocene to lowest Pleistocene continental deposits of the Guadix basin, southern Spain

Abstract: Minwer‐Barakat, R., García‐Alix, A., Suárez, E.M., Freudenthal, M. & Viseras, C. 2012 xx xx: Micromammal biostratigraphy of the Upper Miocene to lowest Pleistocene continental deposits of the Guadix basin, southern Spain. Lethaia, Vol. 45, pp. 594–614. Recent study of the small mammals (rodents and insectivores) from several fossil‐bearing sites situated in the central sector of the Guadix Basin (Southern Spain) has notably increased the knowledge of the mammal assemblages that existed in Southern Iberia from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 58 publications
(134 reference statements)
1
31
0
2
Order By: Relevance
“…This age estimate is confirmed by the presence of Apocricetus alberti Freudenthal, Mein, and Martín Suárez, 1998, Ruscinomys schaubi Villalta and Crusafont, 1956, Paraethomys meini (Michaux, 1969 and Apodemus gudrunae van de Weerd, 1976(Freudenthal et al 1998Sesé 2006a;García-Alix et al 2008a). This faunal association is consistent with the Apodemus gudrunae Assemblage Zone in the Guadix Basin (Minwer-Barakat et al 2012 of Stephanomys dubari Aguilar, Michaux, Bachelet, Calvet, and Faillat, 1991, Weerd, 1976(Mein et al 1990Adrover et al 1993).…”
Section: Geological Settingmentioning
confidence: 48%
“…This age estimate is confirmed by the presence of Apocricetus alberti Freudenthal, Mein, and Martín Suárez, 1998, Ruscinomys schaubi Villalta and Crusafont, 1956, Paraethomys meini (Michaux, 1969 and Apodemus gudrunae van de Weerd, 1976(Freudenthal et al 1998Sesé 2006a;García-Alix et al 2008a). This faunal association is consistent with the Apodemus gudrunae Assemblage Zone in the Guadix Basin (Minwer-Barakat et al 2012 of Stephanomys dubari Aguilar, Michaux, Bachelet, Calvet, and Faillat, 1991, Weerd, 1976(Mein et al 1990Adrover et al 1993).…”
Section: Geological Settingmentioning
confidence: 48%
“…This basin was part of the corridors connecting the Atlantic and Mediterranean seas during part of Miocene (see general sedimentary schemes by Fern andez et al, 1996;Soria et al, 1998). Towards the end of the Miocene the basin was disconnected from the sea and continental successions were deposited (Minwer-Barakat et al, 2009a, 2009b, 2012a, 2012bHüsing et al, 2010Hüsing et al, , 2012Martín-Su arez et al, 2012). Thus, these successions provide an almost continuous continental record for the last 6 Ma.…”
Section: Introduction: the Guadix-baza Basinmentioning
confidence: 96%
“…To date, three formations have been distinguished in the continental deposits: the Guadix Formation, which is mainly fluvial; the Gorafe-Huélago Formation, which is lacustrine; the lacustrine-palustrine Baza Formation (Guerra-Merchán 1990). The basin has been studied in detail (see Oms et al 2011;Minwer-Barakat et al 2012) since Fallot et al (1950) first reported the presence of mammal fossils, and especially since De Bruijn (1973) published his report on the first fossil micromammal localities.…”
Section: Introductionmentioning
confidence: 99%